Infinite Learning Cooperation Program Design Strategy with Ministries, Institutions, Regional Work Units or Institutions (KLDI) - Yuliana Shintia (ConCEPt - Conference on Community Engagement Project, 2024)
This report discusses the implementation of collaboration between InfinitLearning and KLDI in developing training modules that comply with SKKNI. This design aims to increase cooperation and communication between government agencies and improve the efficiency of data handled by agencies and ministries. By implementing a module design strategy, Infinite Learning succeeded in creating an effective and efficient work process, building a strong collaboration culture, and improving KLDI's communication skills. Evaluation after implementation shows success in achieving the strategic goals of the collaboration.